PERSEPSI APOTEKER TERHADAP PERAN DAN TANGGUNG JAWAB DALAM PELAYANAN FARMASI KLINIS DI SITUBONDO - Wicaksono, Agung Budi (HYPOTHESIS : Multidisciplinary Journal Of Social Sciences, 2025)
This study aims to explore pharmacists’ perceptions of their roles and responsibilities in the provision of clinical pharmacy services. Pharmacists’ perceptions are a crucial factor influencing the quality of pharmaceutical care delivered to patients, particularly in ensuring patient safety and promoting rational drug use. Positive perceptions are expected to encourage pharmacists to actively and professionally engage in healthcare services. This study employs a mixed-methods approach, combining quantitative and qualitative methods. Quantitative data were collected using a structured questionnaire to describe the level of pharmacists’ perceptions, while qualitative data were obtained through in-depth interviews to gain a deeper understanding of pharmacists’ experiences and viewpoints. Data analysis was conducted using descriptive statistical analysis and thematic analysis in accordance with the characteristics of each method. The primary expected output of this research is a scientific publication in a nationally accredited journal, which may serve as a reference for the development and improvement of clinical pharmacy services in Indonesia.